Customer Disputes, Misconduct, and Reputation Building in the Market for Financial Advice - Anna Ulrichshofer; Markus Walzl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
We analyze the impact of records of denied and withdrawn customer complaints on job separation in a dataset based on FINRA's Broker-Check database with more than 3 mio. financial advisers. Compared to misconduct that actually leads to a conviction of the adviser, denied and withdrawn complaints are more likely to be repetitive (an adviser with a record is six times more likely to have another incidence of the same kind than the average adviser). This is in-line with the observation that advisers with a record are only slightly (~ 5%) more likely to loose their job. In contrast, an adviser with a record is 42 times more likely to be re-employed compared to advisers without a record. Moreover, reemployment probabilities display a gender-gap but not a gender-punishment gap: There is a 47% smaller reemployment probability for female compared to male employees but this gender-gap is insensitive to the existence of a record of a customer dispute.
Keywords: G34; J44; J71; M51; 330; Financial advice; misconduct; job-mobility; gender-gap; discrimination; credence goods